The long ago : [large type] a novel - McGarrity, Michael (Thorndike Press Large Print Mystery, 2023)
"Growing up in Montana, siblings Raymond and Barbara Lansdale held their chaotic world together through their shared childhood fantasy of The Long Ago: a distant place where happiness and tranquility reigned, far from the dysfunction at home. But imagination only goes so far. To escape his painful past, Ray joins the army and finds a career that gives him a sense of purpose and the promise of adventure. Recent news of his kid sister's disappearance brings Ray home on leave before beginning a stateside assignment almost certain to send him back into the jungles of Vietnam. Determined to find Barbara despite a police investigation that has led nowhere, Ray embarks on a relentless search that takes him from the majestic Montana ranchlands and glitter of Hollywood to the mean streets of L.A. and beyond. As time dwindles, he must confront his worst nightmare. What if Barbara's search for The Long Ago ended in a shallow, unmarked grave, not in the carefree life she'd once so longed for and imagined? A spin-off from McGarrity's nationally best-selling Kevin Kerney family saga, The Long Ago is a richly crafted and enthralling story of grit, determination, and the enduring, restorative strength of love" --